(3bdGOI GdfMQ aj hajGJ CYjGf GdOgQs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s
(3ChdgG (B:s
(3GdYTQhf GdKGfjI ef GdeGFI GdQGHYI CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROi CHh LYaQ GdWMGhi s
(3BNQgG (B:s
(3BNQg fGbU hBNQ GdehLhO efg ai MhGOK GdSfI GdMGOjI hGdKeGfjf HYO GdNeSeGFI (B:" (3hajG Jhai ESeGYjd Hf HcQ GdeYQha HGHf Yha GdRgQi GdCScfOQGfi GdeGdci hGdEeGe YHO GdQMef Hf YHO Gddg s
(3GdLRA GdKGfi ef fSNI CNQis
(3cJHJ QDhS GdJQGLe HGdMeQI YdjgG JedcGJ CbOegG SfI (B1088(3HGSe ehdGfG YR GdOjf eMeO Hf CejQ GdeDfjf GdeJhcds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
Keywords: (3GdJGQjNs